2010
DOI: 10.1001/archinternmed.2010.407
|View full text |Cite
|
Sign up to set email alerts
|

National Estimates of Emergency Department Visits for Hemorrhage-Related Adverse Events From Clopidogrel Plus Aspirin and From Warfarin

Abstract: These findings indicate that the acute hemorrhagic risk with DAT is clinically significant and reinforce the importance of practitioners and patients recognizing and anticipating this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 43 publications
1
60
0
2
Order By: Relevance
“…All our patients underwent a dual antiplatelet therapy during 3 months that was continued as a monotherapy for 3 more months. Dual antiaggregation is known to increase the risk of general hemorrhagic complications 15 ; in particular, the occurrence of cerebral bleeding appears in correlation with the level of platelet inhibition. 16 Fortunately, none of our patients sustained delayed cerebral hemorrhagic events.…”
Section: Discussionmentioning
confidence: 99%
“…All our patients underwent a dual antiplatelet therapy during 3 months that was continued as a monotherapy for 3 more months. Dual antiaggregation is known to increase the risk of general hemorrhagic complications 15 ; in particular, the occurrence of cerebral bleeding appears in correlation with the level of platelet inhibition. 16 Fortunately, none of our patients sustained delayed cerebral hemorrhagic events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that the rate of spontaneous acute bleeding events resulting in hospitalization secondary to antiplatelet therapy was not significantly different compared with warfarin, especially GI bleeding. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, some of the most commonly reported drug-associated adverse events are warfarin related. 2 An important part of interindividual dose variability arises from variation in 2 genes, CYP2C9 and VKORC1. These genes are associated with the pharmacokinetics (affecting drug metabolism) and pharmacodynamics (affecting drug target) of warfarin, respectively.…”
Section: Historical Considerationsmentioning
confidence: 99%